A rare case of primary signet‐ring adenocarcinoma of anorectal region in a young patient: Diagnostic challenges and therapeutic outcomes - Bisma Shaikh; Areeba Gul; Ajeet Singh; Hamza Irfan; Tooba Ali; Riyan Karamat; Aymar Akilimali (Clinical Case Reports)
Key Clinical Message Primary signet‐ring cell carcinoma of the anal canal and rectum is an extremely rare and aggressive malignancy. The present case underscores the importance of considering primary signet‐ring cell carcinoma in differential diagnoses for young patients with chronic anorectal symptoms. It highlights the need for a multidisciplinary treatment approach (including surgery, chemotherapy, and radiotherapy) and comprehensive follow‐up for managing this challenging condition and improving long‐term patient outcomes. Abstract Primary signet‐ring cell carcinoma of the anal canal and rectum is an exceedingly rare subtype of colorectal adenocarcinoma, often originating as an extension of rectal adenocarcinoma. This malignancy constitutes a small fraction of colorectal cancers and is scarcely reported in medical literature. We present the case of an 18‐year‐old male with a three‐year history of progressively worsening hematochezia, anorectal pain, and defecation‐associated prolapse. Initial conservative treatments failed, leading to further investigations that revealed a palpable, nodular anorectal mass. Imaging studies (including CT and MRI), and biopsy confirmed poorly differentiated adenocarcinoma with signet‐ring cell morphology. The tumor exhibited extensive lymphovascular invasion and involved perirectal lymph nodes, and was staged as pT3, N2a. Immunohistochemical staining was positive for CK 7, CK 20, and SATB2, supporting the primary anorectal origin. The treatment regimen included initial diversion colostomies for symptom relief, followed by neoadjuvant chemotherapy with a modified 5‐fluorouracil, leucovorin, irinotecan, and oxaliplatin (FOLFIRINOX) regimen and concurrent chemoradiation with Xeloda. The patient subsequently underwent an abdominoperineal resection (APR), which confirmed the diagnosis and achieved curative resection. Postoperative complications included transient ileus and wound infection, which were managed with supportive care. This case underscores the diagnostic and therapeutic challenges posed by primary signet‐ring cell carcinoma of the anorectal region, highlighting the need for a high index of suspicion and comprehensive diagnostic workup in atypical presentations. The multimodal treatment approach, incorporating surgery, chemotherapy, and radiotherapy, was crucial in managing this locally advanced tumor. The rarity and aggressiveness of this carcinoma necessitate a tailored treatment strategy to improve patient outcomes. Long‐term follow‐up, including regular imaging and surveillance, is vital for monitoring disease recurrence and evaluating treatment effectiveness.